Literature Review: Soft Skill Needed by Gen Z in the Era RI 4.0 and Society 5.0 - Dingot Hamonangan Ismail; Joko Nugroho; Teti Rohayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Generation Z is about to enter the world of work and business. Apart from having many unique qualities and advantages compared to other generations, especially in terms of hard skills in the field of technology, Gen Z is also identified to have a number of weaknesses, particularly in the area of soft skills. This study aims to identify the soft skills needed by Gen Z to succeed in entering the world of work and business in the era of Industry 4.0 and Society 5.0. The research is based on a literature review, referring to various reputable international journal publications and nationally accredited Sinta journals, especially those published since 2019, as well as relevant books on soft skill theory.